An unusual presentation of chronic lymphocytic leukemia/small lymphocytic lymphoma on mammography: Case report. Issue 7 (6th July 2021) - Mohamed, Anas; Younes, Ahmed I.; Stalls, Stephen; Kousar, Aisha; Li, Tian
Abstract: Although rare, breast CLL/SLL should be considered in the differential diagnosis of a breast mass. A high index of suspicion is needed to differentiate this neoplasm from more common breast carcinomas like solid variant of invasive lobular carcinoma. Abstract : Although rare, breast CLL/SLL should be considered in the differential diagnosis of a breast mass. A high index of suspicion is needed to differentiate this neoplasm from more common breast carcinomas like solid variant of invasive lobular carcinoma.